Experimental study on grout defects detection for grouted splice sleeve connectors using stress wave measurement. (8th March 2021) - Xu, Bin; Fan, Xinling; Wang, Haidong; Zhou, Shaojie; Wang, Chen; Chen, Hongbing; Ge, Hanbin
Highlights: Stress wave based grout defects detection approach for GSS is proposed. The feasibility was validated experimentally for two typical GSS specimens with defects. The detectability of different actuator and sensor installation scenarios is discussed. Test results indicate grout defect leads to obvious variation in sensor measurement. The relationship of an evaluation index with the grout defect dimension is determined. Abstract: Grouted splice sleeve (GSS) connectors have been widely employed to connect rebars in prefabricated concrete (PC) structures. However, grout defects may occur due to manual operation miss or poor control approaches for quality, which weaken the efficient embedment of rebars in GSS connectors and lead to a negative effect on mechanical properties of PC structures. The development of reliable and efficient grout defect detection methods for GSS connectors is challenging because its inaccessibility and inner structure complexity. In this paper, an active grout defects detection approach for GSS connectors using direct stress wave measurement is proposed, where piezoelectric-lead-zirconate-titanate (PZT) patches are mounted on the surface of the sleeve as actuators and sensors, and experimental study is carried out to validate its feasibility. Stress wave propagating along the GSS connectors excited by the surface-mounted PZT actuator is measured with PZT sensors. In order to investigate the effect of grout defects on stress wave measurement, four GSS specimens with different degrees of mimicked grout defects are designed and analysis on the PZT sensor measurement with a pitch and catch pattern is carried out. By comparing the PZT sensors measurement of different specimens without and with different grout defects under an identical impulse excitation signal, the grout defect is detected. The relationship between a normalized defect evaluation index (DEI) determined by the use of the PZT sensor measurement and the grout defect severity is analyzed. Experimental results indicate grout defect leads to increase in PZT sensors measurement compared with that of specimen without grout defect. The results show that the proposed approach based on stress wave measurement is efficient in detecting grout defect and the stress wave measurement is sensitive to the dimension of grout defect in GSS.